Complex method of formation of polyprofessional competences of graduate of modern university for sustainable development - Koklevsky, Alexander V. (Journal of the Belarusian State University. Journalism, 2019)
The article presents the author’s complex method of forming polyprofessional competencies of graduates of a modern university for the purposes of sustainable development. The results of the analysis of the level of formation of the polyprofessional competencies of students before applying the author’s methodology in the educational process are presented. The content of the stages of the complex methodology is disclosed. Types, forms, methods, technologies and means of education, contributing to the effective formation of the system of polyprofessional competencies among students used in the educational process of the university on the basis of the model developed by the author are substantiated. The article presents the pedagogical experience of the author of the article on the application of a complex method of forming the polyprofessional competences of students in the process of studying psychological and pedagogical disciplines in a classical university. The educational potential of these disciplines, ensuring the effective formation of polyprofessional competencies, is considered. Intermediate results of the research are presented, confirming the importance of a complex method of forming an integrated system of polyprofessional competencies for sustainable development.
Keywords: complex method; the formation of polyprofessional competencies; students; sustainable development